An exploration of the perceived impact of COVID-19 on physical activity of Irish adolescents - Ng, Kwok; Britton, Una; O’Brien, Wesley; McFlynn, Paul; Connolly, Sinead; Murphy, Marie H.; Woods, Catherine (Springer Science and Business Media LLC, 2025)
Background Physical activity (PA) behaviours of adolescents were impacted by the stringent measures designed to prevent the spread of COVID-19, but little is known about the long-term impact of the pandemic on PA.
Purpose This study examines the perceived impact of COVID-19 on PA, the factors associated with these perceptions, and association with current PA behaviour.
Methods National representative sample from the island of Ireland completed the Children Sport Participation and Physical Activity (CSPPA) study in spring 2022. Questions included the ‘perceived impact of COVID-19 restrictions' dimensions of PA and PA participation. Rasch analyses were used to determine item validity. Logistic regressions were used to determine risk and protective factors in the perceived positive impact and associations between the impact of COVID-19 and PA.
Results The scale was deemed reliable (α = 0.86, p < .001) among the final sample of 12–20 year olds (weighted n = 2888). Perceived positive impact was lowest in school sport as PA levels increased and impact on fitness were highest among adolescents who were daily active (OR = 3.8, CI 2.7–5.3).
Discussion The pandemic had long lasting effects on adolescents’ PA and health. Ways to overcome the lack of school sport during the pandemic is needed at post-primary school level. Making changes to school sport may be protective over low PA levels when considering the return from the pandemic.